Nonvalue of cold enrichment of stools for isolation of Yersinia enterocolitica serotypes 3 and 9 from patients. - Van Noyen, R (1980)
During an 8-year period 14,092 fecal specimens and 1,428 excised appendixes were examined for the presence of Yersinia enterocolitica, with different combinations of direct plating media and enrichment techniques. The combination of direct plating on SS agar and 2 days of enrichment in a modified Rappaport broth at room temperature resulted in the isolation of 100% of serotype 3 and 9 strains. Such strains were recovered from 3.7% of our fecal specimens. Cold enrichment in phosphate buffer further increased the isolation rate, but the additional isolates all belonged to biotype 1. Evidence is presented that biotype 1 strains, at least in Belgium, are not pathogenic for humans. There was a significant affinity of serotype 9 strains for patients suffering from an "appendicular syndrome."